Role of BAG3 in cancer progression: A therapeutic opportunity. (June 2018) - De Marco, Margot; Basile, Anna; Iorio, Vittoria; Festa, Michelina; Falco, Antonia; Ranieri, Bianca; Pascale, Maria; Sala, Gianluca; Remondelli, Paolo; Capunzo, Mario; Firpo, Matthew A.; Pezzilli, Raffaele; et al.
Highlights: BAG3 protein is intracellularly expressed in several tumour types. Intracellular BAG3 can sustain survival and regulate autophagy and motility in cancer cells. BAG3 can be secreted by pancreatic ductal adenocarcinoma (PDAC) cells and, possibly, other tumour types. Secreted BAG3 can bind and activate microenvironment macrophages, mediating a pro-tumour paracrine circuit. BAG3 neutralisation has been proposed as a novel strategy for PDAC therapy. Abstract: BAG3 is a multifunctional protein that can bind to heat shock proteins (Hsp) 70 through its BAG domain and to other partners through its WW domain, proline-rich (PXXP) repeat and IPV (Ile-Pro-Val) motifs. Its intracellular expression can be induced by stressful stimuli, while is constitutive in skeletal muscle, cardiac myocytes and several tumour types. BAG3 can modulate the levels, localisation or activity of its partner proteins, thereby regulating major cell pathways and functions, including apoptosis, autophagy, mechanotransduction, cytoskeleton organisation, motility. A secreted form of BAG3 has been identified in studies on pancreatic ductal adenocarcinoma (PDAC). Secreted BAG3 can bind to a specific receptor, IFITM2, expressed on macrophages, and induce the release of factors that sustain tumour growth and the metastatic process. BAG3 neutralisation therefore appears to constitute a novel potential strategy in the therapy of PDAC and, possibly, other tumours.